2006
DOI: 10.1073/pnas.0509324103
|View full text |Cite
|
Sign up to set email alerts
|

Orphaned ryanodine receptors in the failing heart

Abstract: Heart muscle is characterized by a regular array of proteins and structures that form a repeating functional unit identified as the sarcomere. This regular structure enables tight coupling between electrical activity and Ca 2؉ signaling. In heart failure, multiple cellular defects develop, including reduced contractility, altered Ca 2؉ signaling, and arrhythmias; however, the underlying causes of these defects are not well understood. Here, in ventricular myocytes from spontaneously hypertensive rats that deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

39
469
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 406 publications
(527 citation statements)
references
References 59 publications
39
469
1
3
Order By: Relevance
“…Therefore, the lack of differences observed between the groups after ISO may result from the inherent limitations. On the other hand, fluo-4 has been widely used for intracellular Ca 2ϩ measurement in cardiac myocytes (25). We also found that loss of SLN function resulted in an increase in rate of contraction in isolated atria.…”
Section: Discussionsupporting
confidence: 50%
“…Therefore, the lack of differences observed between the groups after ISO may result from the inherent limitations. On the other hand, fluo-4 has been widely used for intracellular Ca 2ϩ measurement in cardiac myocytes (25). We also found that loss of SLN function resulted in an increase in rate of contraction in isolated atria.…”
Section: Discussionsupporting
confidence: 50%
“…Gomez et al showed that receptor concentrations, receptor properties, and SR calcium concentrations remained the same between control and hypertrophied myocytes and consecutively demonstrated that the decrease in [Ca] i was most consistent with partial uncoupling of the L-type calcium channel and ryanodine receptor through increased inter-receptor distance [33]. This process of 'orphaned ryanodine receptors' and disruption of EC coupling was described more recently by Song et al as a model for Ca 2+ dyssynchrony in heart failure [36]. Such a change in the micro-architecture of the dyad would lead to ineffective signaling and result in hypertrophy.…”
Section: Discussionmentioning
confidence: 86%
“…However, pathological conditions such as heart failure with altered RyR sensitization1 and structure cluster and T‐tubule–SR organization35, 36, 37, 38, 39, 40 could undermine these intrinsically beneficial effects and contribute to cardiac dysfunction and arrhythmogenesis.…”
Section: Discussionmentioning
confidence: 99%